The Role of an Accessory Protein Family in Type VI Secretion - Sachar, Kartik (My University, 2022)
The type VI secretion system (T6SS) is a widely distributed protein nano-machinery found in Gram-negative bacteria. T6SSs are a harpoon-like apparatus that delivers toxic effector proteins directly into target cells in a contact-dependent manner. These effectors are associated with a diverse range of functions such as cytoskeletal modification, biofilm formation, and bacterial competition. Effectors are loaded onto the T6SS by interacting with its structural components. Often, additional accessory proteins are needed for the secretion of these effector proteins. Despite their importance, the direct role of these accessory proteins in the assembly of the T6SS warhead or its subsequent ‘firing’ is unclear. One such example is the putative DUF2169 family of proteins. These proteins are required for effector secretion, however, the molecular function of DUF2169 proteins remains unknown. I have shown that DUF2169-encoding genes co-occur with the structural components of T6SS, such as VgrG and effectors that possess a specialized N-terminal PAAR-like domain. Using a Pseudomonas aeruginosa T6SS-associated gene cluster, I show the network of protein interactions with DUF2169 and these T6SS structural components. Furthermore, I was able to show that these gene clusters form a conserved synteny. Multiple proteins encoded within DUF2169 syntenies are predicted to mimic previously characterized proteins associated with T6SS function. Lastly, using X-ray crystallography I was able to solve the structure of DUF2169 from Vibrio xiamenensis as the first representative of the DUF2169 protein family. Additionally, using structural predictions I show the molecular interaction between DUF2169 and PAAR-like domains of effectors as a potential chaperone. Gaining structural insight into the role of this protein will not only enhance our understanding of T6SS function but also highlight the mechanistic differences between different T6SS warheads. Since T6SSs can deliver a variety of proteins into both prokaryotic and eukaryotic cells, understanding how this delivery mechanism works expands our knowledge of how bacteria interact with diverse cell types. Furthermore, uncovering a new mechanism for directly delivering proteins into different cell types has valuable potential for medical and industrial applications.